Statistical optimization and characterization of acoustically extracted ananas comosus peel powder with enhanced antioxidant capacity - Yahya N.A.; Wahab R.A.; Hamid M.A.; Mahat N.A.; Huri M.A.M.; Attan N.; Hashim S.E. (Penerbit UTM Press, 2024)
Ananas comosus (L.) Merr is one of many commercially popular fruits in the cannery food industry that contributes to the increasingly mounting agro-industrial waste. In this study, a four−factor−three−level Box−Behnken design (BBD) that comprised of sonication time (A), solvent ratio (B), amplitude (C) and liquid−solid ratio (D) for the ultrasound−assisted extraction (UAE) of pineapple peels (PP) was utilized to optimize the yield of total phenolic content (TPC). Under an optimized UAE condition [5 min; 50 % of ethanol: water; 65 % of amplitude; 35:1 mL/g of liquid−solid ratio], the highest TPC from PP of 708.10 mg gallic acid equivalent (GAE)/g DW was achieved. Antioxidant capacity analysis of PP revealed a high total flavonoid content (TFC) with the IC50 for 2,2−diphenyl−1−picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) of 1146.86 ± 11.83 mg QE/g, 11.83 mg/mL and 1578.07 ± 25.96 µM Fe (II)/100g, respectively. High-performance liquid chromatography (HPLC) analysis revealed that the major flavonoid in the phenolic profile of PP extracts being catechin followed by quercetin and gallic acid. The UAE of PP extracts exhibited higher TPC than known conventional extraction techniques, thus indicating its efficacy to recover satisfactory quantities of phenolics in PP under optimized conditions. © 2020 Penerbit UTM Press. All rights reserved.